Fostering behaviour change for pandemic prevention and control through public space designs in Hefei, China - Liu, Jing (2022)
Due to urbanisation and globalisation, pandemics and their devastating impacts have triggered an unprecedented crisis in all spheres of human society. Currently, people across the globe have suffered from several waves of the Coronavirus Disease 2019 (COVID-19) pandemic, so it is highly significant to develop public health solutions for pandemic prevention and control. In addition to antiviral medicines and vaccines, protective behaviours, such as face mask-wearing, hand hygiene, social distancing, and contact reduction can also limit the spread of viruses. Currently, authorities have launched policies and legislation to promote public behaviour change. However, many people in Hefei, China have difficulties adhering to performing the recommended protective behaviour during pandemics. One main reason is that current design interventions cannot play a role in prompting people’s behaviour change for pandemic prevention and control. Hence, this study strives to develop a research framework and propose strategies to improve the current design interventions in public spaces, and finally provide support for people’s pandemic-related behaviour change. The disadvantageous condition and successful pandemic prevention experience have made Hefei a fit laboratory for conducting pandemic-related research. Four studies were carried out to achieve the research objective. First, this study examined the existing pandemic situation in public spaces in Hefei, China. After that, the researcher identified seven key challenges and six design limitations of behaviour change during pandemics and then prioritized them through three Nominal Group Technique (NGT) discussions. Second, based on the literature review and user interview results (N=22), this study determined nine key factors influencing people’s behaviour change. These key factors were categorized into four main aspects: perceptional factors (attitudes, subjective norms and perceived behaviour control, risk perceptions), social factors (knowledge and information dissemination, governmental regulations), physical factors (tools and facilities and surveillance), and sociocultural factor (cultural contexts). Third, this research developed a behaviour change framework that reveals people’s behaviour change intention and formation process during pandemics. After that, the researcher carried out an empirical study (N=549) to quantify relationships among variables in the behaviour change framework and further improve it. A Structural Equation Modeling (SEM) approach was employed during this process. According to the above findings, the researcher forwarded a strategic public design framework to promote pandemic-related behaviour change. Finally, the frameworks were validated by an expert survey (N=5). Overall, this study explores the potential of integrating public health, behaviour science, and design science under a pandemic context, contributing to the knowledge of “design for behaviour change” and “design for pandemic prevention and control”. The proposed research framework is an integration, extension and improvement of the previous behaviour theories, as well as implementation under a new context. Besides, this study provides valuable insights for different stakeholders, including designers, policymakers, and administrators in public spaces when dealing with pandemic situations.